Answer:
(3, -2)
Step-by-step explanation:
The <em>midpoint</em> of two points is half-way between the x-values and the y-values.
The formula is
M = ((x₁ + x₂)/2, (y₁ + y₂)/2)
For the points (5,-5) and (1,1),
Half way between the x values is
(x₁ + x₂)/2 = (5 + 1) /2 = 6/2 = 3
Half way between the y values is
(y₁ + y₂)/2= (-5 + 1)/2 = -4/2 = -2
M = (3, -2)
The graph below shows your two points at (5,-5) and (1,1) and the mid-point at (3, -2).
Answer:
external conflict
Step-by-step explanation:
It will take 9 hours because 3 times 9 is 27
The answer is 63 cm bc 30 60 90 triangles have a rule where the short leg is x longer is x√3 and the hypotenuse is x2
you can see this if you imagine the triangle as equilateral then cutting it in half
Answer:
Quadratic expression
Step-by-step explanation:
5x + 3x^2 − 7
Degree of expression = 2
So it is Quadratic expression